Spain's Party System at Times of the Economical Crisis after 2008 - Myśliwiec, Małgorzata (Political Preferences, 2015)
In reality of representative democracy, the economic situation of the state is one of the most important factors determining the stability and durability of a political system. In 2008 an intense economic crisis affected whole Europe. One of consequences of this situation were serious changes in composition and functioning of political systems and its subsystems in almost all countries belonging to the region. This phenomenon has also occurred in contemporary Spain. The main aim of this paper will be to show how the Spanish party system has changed after the outbreak of the economic crisis of 2008. Key words: political parties, party system, economical crisis